Comportamiento de la función renal en el adulto mayor - Yilena Liy Rodríguez; Gretel Pino Rivera; Lissette Sánchez Pérez; Yuroska González Perez; Rafael Chacón Martínez (Correo Científico Médico)
RESUMEN